2012
DOI: 10.1021/ja300868e
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Spin Transition in Nanosize Stoichiometric Lithium Cobalt Oxide

Abstract: A change in the electronic spin state of the surfaces relevant to Li (de)intercalation of nanosized stoichiometric lithium cobalt oxide LiCo(III)O(2) from low-spin to intermediate and high spin is observed for the first time. These surfaces are the ones that are relevant for Li (de)intercalation. From density functional theory calculations with a Hubbard U correction, the surface energies of the layered lithium cobalt oxide can be significantly lowered as a consequence of the spin change. The crystal field spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
148
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(164 citation statements)
references
References 15 publications
16
148
0
Order By: Relevance
“…The combination of the magnetization, Bader charges, and PDOS analysis indicates Co 3+ in an intermediate spin state. This result is in agreement with previous work 21,36 showing experimental 37 and theoretical evidence of intermediate spin of the five coordinated Co 3+ ions at the surface of LCO. 21 Other previous work 35 has also found that changes in the coordination symmetry around Co ions change its electronic configuration, as expected.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The combination of the magnetization, Bader charges, and PDOS analysis indicates Co 3+ in an intermediate spin state. This result is in agreement with previous work 21,36 showing experimental 37 and theoretical evidence of intermediate spin of the five coordinated Co 3+ ions at the surface of LCO. 21 Other previous work 35 has also found that changes in the coordination symmetry around Co ions change its electronic configuration, as expected.…”
Section: Resultssupporting
confidence: 93%
“…High spin states of Co 3+ at LCO (104) surfaces, with square pyramidal coordination, have been reported. 38 Qian et al 21 found that the surface energies are minimized when the surface Co 3+ value found for LCO since NMC111 has a lower concentration of Co 3+ . The rest of the TMs (Ni 2+ and Mn 4+ ) do not present any change in spin state because they are already in high spin states at these oxidation states.…”
Section: Resultsmentioning
confidence: 99%
“…Representative EELS spectra of the pristine 9 nm sample are shown in Figure 2a and b, where the position of EELS acquisition is shown in Figure S2 (SI). The Co L 3 /L 2 ratios of ∼2.7 were comparable to those of our previous XPS results, 21 indicative of a Co oxidation state of 3+, and no noticeable changes in the Co L 3 / …”
supporting
confidence: 88%
“…21 The ORR and OER activities and pseudocapacitance of these rodshaped LiCoO 2 were studied in 0.1 M KOH. Higher specific ORR and OER activities accompanied by higher charge transferred per surface area during Co 2+/3+ and 3+/4+ redox processes were found at the tips, compared with the side surfaces.…”
mentioning
confidence: 99%
“…Binding energies, redox-potentials and hopping barriers can strongly deviate from the bulk value near surfaces and in subsurface regions [48,58,59,60]. Especially for materials with 1D diffusion, the crossing of the orthogonal surface planes can have tremendous effects on the performance, and theoretical computations succeeded in correctly describing appropriate surface modifications for improved material properties [58].…”
Section: Interfaces In Batteriesmentioning
confidence: 99%